2010
DOI: 10.1111/j.1365-3040.2010.02207.x
|View full text |Cite
|
Sign up to set email alerts
|

Turning over a new ‘leaf’: multiple functional significances of leaves versus phyllodes in Hawaiian Acacia koa

Abstract: Hawaiian endemic tree Acacia koa is a model for heteroblasty with bipinnately compound leaves and phyllodes. Previous studies suggested three hypotheses for their functional differentiation: an advantage of leaves for early growth or shade tolerance, and an advantage of phyllodes for drought tolerance. We tested the ability of these hypotheses to explain differences between leaf types for potted plants in 104 physiological and morphological traits, including gas exchange, structure and composition, hydraulic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 82 publications
5
56
0
Order By: Relevance
“…Previous studies found these criteria to be sufficient for the stabilization of transpiration rate, water potential, and K leaf . Tests for any change in transpiration rate, leaf water potential, and K leaf with measurement time (after stable flow was established) across leaves of a given species for seven species with a wide range of leaf capacitance showed no relationship of K leaf to measurement time (Scoffoni et al, 2008;Pasquet-Kok et al, 2010).…”
Section: Empirical Measurements Of K Oxmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies found these criteria to be sufficient for the stabilization of transpiration rate, water potential, and K leaf . Tests for any change in transpiration rate, leaf water potential, and K leaf with measurement time (after stable flow was established) across leaves of a given species for seven species with a wide range of leaf capacitance showed no relationship of K leaf to measurement time (Scoffoni et al, 2008;Pasquet-Kok et al, 2010).…”
Section: Empirical Measurements Of K Oxmentioning
confidence: 96%
“…In particular, the evaporative flux method requires steady-state transpiration and stable leaf water potential to enable the determination of K leaf . We followed the procedure tested and established for a wide range of species in previous work (Scoffoni et al, 2008Pasquet-Kok et al, 2010;Guyot et al, 2012). In measuring K leaf , 30 min was chosen as a minimum to ensure that leaves had acclimated to high irradiance and stomatal conductance had stabilized.…”
Section: Empirical Measurements Of K Oxmentioning
confidence: 99%
“…Although the detailed functional trait survey conducted here is relatively novel in its breadth (see also Pasquet-Kok et al 2010), this is a logical extension of the traditional approach for understanding the basis for plant adaptation to environment, i.e. testing expectations for individual traits established by previous studies of the functional significance of these traits in other species.…”
Section: Implications For Drought and Shade Tolerance: Ruscus As A Modelmentioning
confidence: 99%
“…Such traits include a high water-use efficiency (Wright and Westoby 2003), as well as water storage tissue with high water storage capacitance associated with low bulk leaf modulus of elasticity, high relative water content at turgor loss point, and low cuticular conductance (Sack et al 2003a;Pasquet-Kok et al 2010;Ogburn and Edwards 2012). Traits potentially contributing to shade tolerance include low rates of maximum photosynthetic CO 2 assimilation per leaf area and per leaf mass, low light compensation point, low maximum rate of carboxylation, low maximum rate of electron transport, and more negative carbon isotope ratios (Walters and Reich 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple hypotheses have been made to explain the change from true leaves to phyllodes; true leaves may be more important in earlier developmental fast-growing stages, while phyllodes provide the plant higher tolerance to drought (Walters and Bartholomew, 1984;1990;Hansen, 1986;Hansen and Steig, 1993). Pasquet-kok et al (2010) tested these hypotheses on A. koa and observed that true leaves showed higher massbased gas exchange necessary for growth; on the other hand, phyllodes had characteristics for drought tolerance, which is due to greater capacitance of the water storage tissue and its ability to keep stomata closed under hot and dry conditions. Furthermore, the orientation of the leaf types may support these hypotheses; the true leaves, which spread horizontally, absorb more irradiance within small canopies under shadows, whereas the vertically arranged phyllodes protect the plant from intense sunlight (Walters and Bartholomew, 1984;Hansen, 1986;.…”
Section: General Characteristicsmentioning
confidence: 99%